Produção de conhecimento interdisciplinar: contextos e pretextos em programas de Pós-Graduação - Rubin-Oliveira, Marlize (2014)
The main goal of this paper was to analyze interdisciplinary graduate programs, seeking to capture the specific contexts and pretexts confronted by them. The locus of the study were eight interdisciplinary graduate programs accredited and recommended by Brazilian Federal Agency for Support and Evaluation of Graduate Education (CAPES), based on the principle of dialogue between the humanities and the natural sciences and a program at the University of Arizona (U of A) - United States. The analyses identified a close relationship between international movements to rethink modern science and the genesis of the programs. The programs are understood as part of the growing movement of science that seeks to rethink fragmentation and duality and to consider other legitimate positions of power and prestige along with the revision of the organization of knowledge in historically constituted areas.